New programs for translating research to patient care: Lessons learned at the NIH Center for Accelerated Innovations at Cleveland Clinic. Issue 1 (13th September 2021) - Reizes, Ofer; Low, Mark; Josyula, Vara Prasad; Ellis, James; Vince, D. Geoffrey
Abstract: The NIH Center for Accelerated Innovations at Cleveland Clinic (NCAI-CC) was funded by the National Heart Lung and Blood Institute (NHLBI) to support academic investigators in technology development and commercialization. NCAI-CC was one of three multi-institutional Centers established in the fall of 2013. The goal of each Center was to catalyze the growth of an ecosystem of commercialization within their affiliated institutions and regions by managing a program of funding and guiding translational project development and by delivering commercialization education programs to participating investigators. NCAI-CC created and managed such a funding program, ultimately supporting 75 different projects across seven separate academic institutions and developed tailored educational content following the National Science Foundation I-Corps™ curriculum and delivered the program to 79 teams from 12 institutions. We determined early on that in establishment and implementation of projects, it is important to support the teams and principal investigators throughout the program. The support includes a change in principal investigator mindset from specific aims orientation to goals and deliverables on projects. Our skills development efforts emphasized commercialization and a deep understanding of customer needs for new technology adoption. Here, we review our experiences, outcomes, and insights, including the challenges identified in program implementation.